MO784: Racial Differences in Vascular Access for Dialysis—Why are Black Patients Prone to Fewer Vascular Access Options?. (3rd May 2022) - Assis Pereira, Tiago; Barata, Rui; Damas, Juliana; Nolasco, Fernando
Abstract: BACKGROUND AND AIMS: Vascular access (VA) represents a major component for dialysis outcomes, like mortality, morbidity, hospital admission and economical costs. A well-described phenomenon, is the racial disparity concerning vascular access care, as black patients are associated with fewer fistulae construction and a higher rate of access dysfunction. Different clinical and socio-economical factors have been pointed to explain this association, however concrete vascular data has not been explored. We analyse the anatomical and haemodynamic data, obtained by preoperative ultrasound mapping, in order to prove whether vascular differences explain racial disparities. METHOD: Retrospective study that included patients referred for the first VA construction and evaluated through ultrasound vascular mapping. Sociodemographic, clinical, vascular data (arterial diameter and peak systolic velocity, PSV; presence of mono or biphasic flow and significant calcification) and vascular mapping conclusions (type of possible VA) were collected. For racial comparison of collected data, two groups were created, blacks and non-blacks. Appropriate tests for continuous and categorical variables were applied, recurring to SPSS v21.0. Unadjusted and adjusted multivariate logistic regression models were fitted to determine if races are associated with clinical or vascular features. RESULTS: A total of 102 patients were included. The mean age was 67 ± 16 years, 54% were male and 14% were black and 36% were already on dialysis or kidney transplantation. Hypertension, diabetes mellitus, cardiac insufficiency, coronary disease, peripheral arterial disease and obesity were noted at 94, 48, 34, 25, 17 and 35%, respectively. Among these, non-black patients presented a higher risk for cardiac insufficiency (P = 0.025). Concerning arterial evaluation: 16% presented upper brachial bifurcation in one or both arms; 31% presented monophasic or biphasic waveform in any of the principle arterial vessels and 26% presented significant arterial calcification. These qualitative and the radial and brachial diameters and PSV showed no differences between black and non-black patients. Finally, the feasibility for radiocephalic or brachiocephalic was noted in 67%, whilst in 33% only brachiobasilic or prosthetic fistulae was possible. Black race was found as a predictor for these differences, accounting for a higher probability of scarce options (P = 0.042), the effect that was reinforced when evaluating prosthetic fistulae as the only option (P = 0.027); both conclusions persisted in a multivariate analysis including cardiac insufficiency. CONCLUSION: Black patients are associated with scarce VA options, such as brachiobasilic or prosthetic fistulas. No substantial differences were identified in arterial, clinical and sociodemographic features, remaining the venous system as the most disabling component in VA construction. The underlying biology is an area to explore, for academic and practical purposes. A larger sample should be collected to confirm these findings and establish if peripheral venous features underlie racial differences related to VA care in haemodialysis.